2009
DOI: 10.1038/emboj.2009.326
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of α2β1 integrin interaction with human echovirus 1

Abstract: Conformational activation increases the affinity of integrins to their ligands. On ligand binding, further changes in integrin conformation elicit cellular signalling. Unlike any of the natural ligands of a2b1 integrin, human echovirus 1 (EV1) seemed to bind more avidly a 'closed' than an activated 'open' form of the a2I domain. Furthermore, a mutation E336A in the a2 subunit, which inactivated a2b1 as a collagen receptor, enhanced a2b1 binding to EV1. Thus, EV1 seems to recognize an inactive integrin, and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 74 publications
2
56
1
Order By: Relevance
“…If only one integrin conformation can be bound, then there are fewer potential binding partners per cell, but if virus binding then immediately triggered a conformational change (two-state model) leading to integrin signaling and uptake, the probability of entry at this second step would be improved. Echovirus 1, for instance, which binds to the bent ␣ 2 ␤ 1 integrin conformation, causes integrin clustering, probably mediating signaling for endocytosis, and at later time points colocalizes with internalized integrin (15,25,58). It is likely that avidity plays a role in the in vivo situation, resulting in an even higher overall affinity of the virus for the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…If only one integrin conformation can be bound, then there are fewer potential binding partners per cell, but if virus binding then immediately triggered a conformational change (two-state model) leading to integrin signaling and uptake, the probability of entry at this second step would be improved. Echovirus 1, for instance, which binds to the bent ␣ 2 ␤ 1 integrin conformation, causes integrin clustering, probably mediating signaling for endocytosis, and at later time points colocalizes with internalized integrin (15,25,58). It is likely that avidity plays a role in the in vivo situation, resulting in an even higher overall affinity of the virus for the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are involved in the entry of many viruses (2,5,19,21,26,34,36,44,59,64) and bacteria (16,27,40). The pathogen-host interaction may promote the clustering of integrins and focal adhesion formation but subvert the downstream signaling network to modify membrane traffic and cytoskeletal dynamics to meet their own needs (1,17).…”
Section: Discussionmentioning
confidence: 99%
“…CHO cells were stably transfected with expression constructs of wild-type human ␣2 integrin (CHO-␣2wt), ␣2 integrin variants (CHO-␣2Y285F, CHO-␣2E336A, CHO-␣2E318W), or ␣1 integrin expression constructs (17,24,25). In adhesion assays, cells (1.5 ϫ 10 5 cells/well) were allowed to attach to plates coated with rat tail collagen I, collagen IV (BD Biosciences), laminin-332, vitronectin, or ␣-chymotryptic fragments (120 or 40 kDa) of fibronectin (10 g/ml; Chemicon) for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the Glu-336 residue may act as a link between ␣2I and ␤1I domains (16) in a manner similar to that of Glu-320 in ␣M (12,13) and Glu-310 in ␣L (14) and regulate the activity of the receptor. However, the function of ␣2␤1 does not seem to be entirely dependent on conformational activation because ␣2␤1 can bind even a large ligand (human echovirus-1) in a non-activated conformation (17).…”
mentioning
confidence: 99%